Spatio-temporal Variations of Tropospheric Nitrogen Dioxide in Turkey Based on Satellite Remote Sensing - Yavaşlı, Doğukan Doğu (Geographica Pannonica, 2020)
The satellite observations of NO2 acquire the total tropospheric column over an area while the current ground observations lack spatial and temporal coverage. In this study the Dutch Ozone Monitoring Instrument (OMI) NO2 (DOMINO) product for 2004 – 2019 period was used to analyze the spatial and temporal variations of NO2 in Turkey. Considering the seasonality characteristics of NO2, we have used pixel passed seasonal Kendall (S-K) test to investigate the trend of the change. The highest values of NO2 has been found at the metropolitan cities and perimeter of the high capacity power plants in the observed period. The monthly average concentrations of NO2 are higher in winter months due to the higher demand of heating and power usage. S-K trend test results indicate a statistically negative trend at the largest cities such as Istanbul, Ankara and Izmir. However statistically significant positive trend has been found in some areas and Syrian border provinces in particular. Our results show that there is an abrupt change by 2011 in the tropospheric NO2 concentrations, same period when the first Syrian refugees have arrived after the political disorder. The dramatic change at the emission landscape of the NO2 in the region can be attributed to the rapid increase in the number of refugees and increased anthropogenic activity.
Keywords: NO2; OMI; Seasonal Kendall; Turkey; DOMINO data